1985
DOI: 10.2105/ajph.75.10.1219
|View full text |Cite
|
Sign up to set email alerts
|

Self-management education of children with asthma: AIR WISE.

Abstract: This study was conducted to test the efficacy of AIR WISE, an individually administered asthma self-management program. Subjects were paired and randomly assigned to either an experimental group (N =7) or a control group (N =7). The frequency of experimental group emergency visits, analyzed over a 12-month posttreatment period, was substantially less than those of the control group, supporting the hypothesis that AIR WISE is effective in high-utilizer children through improved self-management. (Am J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…For the majority of studies, data were available from one or more published English language journal articles, sometimes accompanied by foreign language papers, conference abstracts, theses and unpublished manuscripts. For two studies data were extracted from unpublished PhD theses (Catrambone, 386 Gold 418 ), for one study data came from a short research report, thesis and two abstracts (McNabb [412][413][414][415] ) and one further study was published as a short research report only (Shields 377 ), but additional abstracts excluded in their own right were consulted to provide additional details on the intervention. [464][465][466][467] All of these were in English.…”
Section: Quantity and Quality Of Information Available For Data Extramentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of studies, data were available from one or more published English language journal articles, sometimes accompanied by foreign language papers, conference abstracts, theses and unpublished manuscripts. For two studies data were extracted from unpublished PhD theses (Catrambone, 386 Gold 418 ), for one study data came from a short research report, thesis and two abstracts (McNabb [412][413][414][415] ) and one further study was published as a short research report only (Shields 377 ), but additional abstracts excluded in their own right were consulted to provide additional details on the intervention. [464][465][466][467] All of these were in English.…”
Section: Quantity and Quality Of Information Available For Data Extramentioning
confidence: 99%
“…Two studies were published in the 1970s (Alexander, 1972, 363 Davis 382,383 ), eight in the 1980s (Alexander, 1988, 402 Backman, 385 Evans, 403 Gold, 418 Gustafsson, 419,420 McNabb, [412][413][414][415] Mitchell, 376 Westphal 410 ), 16 in the 1990s (Colland, 378 Collins, 407 Dahl, 381 Fisher, 408,409 Garrett, 404 Greineder, ). The breakdown of studies by decade of publication according to the main type of intervention evaluated is shown in Figure 4.…”
Section: Publication Datesmentioning
confidence: 99%
“…Youth participated in games, discussed feelings, and were taught about environmental controls, relaxation and breathing exercises, decisionmaking skills, and how to live a balanced life Clinic Traditional education McNabb et al (1985) The AIR WISE program consisted of individually tailored educational sessions that were geared towards teaching youth ways to manage their disease Clinic Traditional education…”
Section: Coding Of Studiesmentioning
confidence: 99%
“…Another program reported that the major cost of the program was hiring a referral coordinator which averaged about $6.66 per treatment per student (Joseph et al 2007). The other two studies reported savings of $180 per youth per year (Lewis et al 1984) and $507 per youth per year (McNabb et al 1985). However, both savings should be viewed with caution because the calculations are approximately 25 years old.…”
Section: Study Outcomesmentioning
confidence: 99%
“…The direct and indirect costs of asthma in 1998 were estimated to be $12.7 billion (4). Evidence suggests that asthma management programs can be effective at reducing hospital and emergency visits and that there may be cost savings associated with such programs (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%